Voltage regulation and power loss reduction by integration of SVC in distribution networks via PSSE - Ba-swaimi Saleh; Lee Jun Yin; Renuga Verayiah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Voltage stability is necessary in order to maintain the health of the grid system. In recent years, the load demand is increasing from time-to-time which compromised the stability of the system. On that purpose, several methods on enhancing the voltage stability of the system was introduced such as the transformer tap and FACTS devices. In a general overview, this study is to propose a several power compensation techniques on the base case of an IEEE-33 bus whereby power flow analysis using Netwon- Raphson in PSS/E software is performed. Afterwards, distributed generation (DG) and Static VAR Compensator (SVC) will be implemented within the distribution network to compensate the voltage instability losses based on the weakest index from the bus system. From both the cases which is proposed earlier, a comparison study is conducted on the performance on both DG and SVC within the proposed network.